Penerapan Aplikasi Game Quizziz untuk Meningkatkan Hasil Belajar Matematika - Rochima Fauqa Muamalah; Deni Adi Putra; Meirza Nanda Faradita (Departement of Mathematics Education, 2023)
This study aims to 1) describe the application of the Quizzing application, which can improve student learning outcomes in mathematics, and 2) describe the increase in student learning outcomes in mathematics after applying learning using the Quizzing application. This research is class action research (CAR). In this study, there are 4 stages: planning, action, observation, and reflection. The subjects of this study were 6th grade students at SD Muhammadiyah 16, Surabaya, totaling 25 students. The instrument used to determine student learning outcomes is a written test. The results of research and discussion, as well as data analysis, can be described, and it can be concluded that the application of online game applications to student learning outcomes has increased. Learning outcomes were obtained by 20% during the pre-cycle, 32% during cycle I, and 100% during cycle II, or all students reached the limit of completion. The conclusions from this study are that: 1) the application of the Quiz application can improve student learning outcomes in mathematics. The suggestion from this study is the need for reinforcement when providing explanations and strengthening the internet network